Synthesis and optimization of palmitoyl-chitosan nanoparticles as a potent dual antioxidant carrier with hydrophobic and hydrophilic compounds - Othman, Nurhanisah (2022)
Chitosan nanoparticles (CNP) is a potent delivery vector for hydrophilic pharmaceuticals as it is biodegradable and biocompatible. In this study, it was synthesized by a non-toxic and simple ionic gelation method that successfully produced cationic, monodispersed spherical particles with an average size of 60.5 ± 2.1 nm and a polydispersity index (PDI) of 0.19 ± 0.02. The carrier was dual encapsulated with antioxidants to diversify CNP ability as it is normally being used for single encapsulation. Hydrophobic thymoquinone (TQ) and hydrophilic L-ascorbic acid (LAA) were incorporated into the carrier to evaluate their combination effects in scavenging free radicals when delivered using a nanoparticle (NP) system. However, the encapsulation of hydrophobic TQ was marred by the hydrophilicity of chitosan (CS). Thus, palmitic acid was conjugated on the CS through hydrophobic modification, which produced palmitoyl-chitosan nanoparticles (PCNP). The amphiphilic PCNP encapsulated with TQ and LAA showed increased size, 247.7 ± 24.0 nm and PDI, 0.35 ± 0.04. It also had a positive zeta potential of 19.60 ± 1.27 mV, which would make good interactions with negatively charged cell membranes during antioxidants delivery. The encapsulation efficiencies (EE) of TQ and LAA increased to 64.9 ± 5.3% and 90.0 ± 0.0%, respectively. The antioxidants followed zero order release kinetics with a controlled release manner for about 48 h. Interaction effect between TQ and LAA loaded in the NP system was determined by classical isobologram (CI) values derived from diphenyl picrylhydrazyl (DPPH) assay. Combined TQ and LAA had CI values of less than one with lower value in the PCNP system than CNP. This indicates that the interaction between those antioxidants showed higher synergistic effects in PCNP, which enhanced DPPH radical scavenging activities. Additionally, reactive oxygen species (ROS) assay was experimented on human normal lung fibroblast cell line, MRC-5 as lungs is one of the organs with high accumulation of free radicals. About 48 h post treatment, the dual loaded TQ and LAA in PCNP showed the lowest ROS level in comparison to single loaded antioxidant and bare antioxidant delivery. The H2O2 radical scavenging was influenced by both controlled release property of the PCNP system and synergy between TQ and LAA. In short, the dual loaded TQ and LAA in the hydrophobically modified PCNP had successfully depicted the capability to hold more than one compound at a time in a single CS based nanocarrier. With this advancement, more highly efficacious compounds of different polarities with poor systemic uptake could be encapsulated together in NP systems to increase their pharmaceutical efficiency.